2005
DOI: 10.1017/s104161020500219x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risperidone in the treatment of behavioral and psychological symptoms and sleep disturbances associated with dementia

Abstract: Risperidone is effective and well tolerated in the treatment of BPSD and associated sleep disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
(41 reference statements)
0
11
1
Order By: Relevance
“…There have been several controlled and open trials that have examined the effectiveness of risperidone for treating BPSD. In an open-label prospective study, Duran et al [13] reported that risperidone treatment was associated with a 63% reduction in the scores on the NPI total scale at week 12, which was lower than our results (76.9%). This discrepancy might be due to differences in the subjects' characteristics, the size of the populations and the treatment periods.…”
Section: Discussioncontrasting
confidence: 99%
“…There have been several controlled and open trials that have examined the effectiveness of risperidone for treating BPSD. In an open-label prospective study, Duran et al [13] reported that risperidone treatment was associated with a 63% reduction in the scores on the NPI total scale at week 12, which was lower than our results (76.9%). This discrepancy might be due to differences in the subjects' characteristics, the size of the populations and the treatment periods.…”
Section: Discussioncontrasting
confidence: 99%
“…It is noteworthy that risperidone, quetiapine and aripiprazole were the most recommended antipsychotics in the over-mentioned types of dementia. Namely, risperidone had the strongest evidence for the treatment of BPSD symptoms in AD and MixD [60,61,62,63], although it carries higher cardiovascular and metabolic risks.…”
Section: Antipsychotic Use Across Dementia Sub-types (Vad Ad Versmentioning
confidence: 99%
“…Pharmacological treatments for aggression and related symptoms in dementia include antipsychotics, certain antidepressants, mood stabilizers and other medications. Antipsychotics are the most commonly prescribed drugs for these symptoms and the most effective, at least in the short term , with risperidone being licensed or approved for short‐term treatment of BPSD in Alzheimer's disease in both Canada and the United Kingdom on the basis of several randomized placebo‐controlled trials .…”
Section: Introductionmentioning
confidence: 99%